International E conference on Current Research Perspectives in Clinical Sciences: Life Sciences-Health - DR. ANTARA BANERJEE, Guest Editor (International Journal of Life Science and Pharma Research, 2021)
In humans, hair is an essential indicator of individual self-image, identity, ethnicity, and health. Loss of hair from any part of the body for any reason is called alopecia. There are several conditions ranging from thinning hair to complete baldness. Alopecia is of two kinds, scarring alopecia and non-scarring alopecia. The scarring alopecia is divided into three types depending on the presence of inflammatory cells like lymphocytic, neutrophilic, and mixed. Scarring alopecias are typically caused by inflammation that destroys the hair follicle leading to irreversible hair loss. While the etiology and pathogenesis of PCA remain unclear, it is currently considered as an inflammatory disorder.